Mitochondrial Damage and Apoptosis Induced by Adenosine Deaminase Inhibition and Deoxyadenosine in Human Neuroblastoma Cell Lines. Issue 7 (28th December 2015) - Garcia‐Gil, Mercedes; Tozzi, Maria Grazia; Balestri, Francesco; Colombaioni, Laura; Camici, Marcella
ABSTRACT: The treatment with deoxycoformycin, a strong adenosine deaminase inhibitor, in combination with deoxyadenosine, causes apoptotic cell death of two human neuroblastoma cell lines, SH‐SY5Y and LAN5. Herein we demonstrate that, in SH‐SY5Y cells, this combination rapidly decreases mitochondrial reactive oxygen species and, in parallel, increases mitochondrial mass, while, later, induces nuclear fragmentation, and activation of caspase‐8, ‐9, and ‐3. In previous papers we have shown that a human astrocytoma cell line, subjected to the same treatment, undergoes apoptotic death as well. Therefore, both astrocytoma and neuroblastoma cell lines undergo apoptotic death following the combined treatment with deoxycoformycin and deoxyadenosine, but several differences have been found in the mode of action, possibly reflecting a different functional and metabolic profile of the two cell lines. Overall this work indicates that the neuroblastoma cell lines, like the line of astrocytic origin, are very sensitive to purine metabolism perturbation thus suggesting new therapeutic approaches to nervous system tumors. J. Cell. Biochem. 117: 1671–1679, 2016. © 2015 Wiley Periodicals, Inc. Abstract : The treatment with deoxycoformycin, a strong adenosine deaminase inhibitor, in combination with deoxyadenosine, causes apoptotic cell death of two human neuroblastoma cell lines, SH‐SY5Y and LAN‐5. In previous papers we have shown that a human astrocytoma cell line, subjected to the same treatment, undergoes apoptotic death as well. This work indicates that the neuroblastoma cell lines, like the line of astrocytic origin, are very sensitive to purine metabolism perturbation thus suggesting new therapeutic approaches to nervous system tumors.